Direct observation of the conical intersection in cis-trans photoisomerization of rhodopsin - Polli, D; Altoè, P; Weingart, O; Kukura, P; Spillane, K; Manzoni, C; Brida, D; Tomasello, G; Orlandi, G; Mathies, R; Garavelli, M; Cerullo, G (2010)
High-time-resolution broadband pump-probe spectroscopy of rhodopsin reveals loss of reactant and appearance of photoproduct features within ≈100fs, which are signatures of a wavepacket moving through a conical intersection. Experiments are supported by molecular dynamics simulations. © OSA / UP 2010.